THE EFFECT OF KAHOOT AS A LEARNING MEDIA ON STUDENTS’ VOCABULARY MASTERY - Natasya Aisyah; Maryati Salmiah (University of Kuningan, 2024)
The purpose of this study was to determine how much influence the kahoot application has in evaluating junior high school students' word mastery which can be improved through the Kahoot application as a learning medium. This study used a quantitative approach. The sample size for this study consisted of 35 junior high school students in one class, namely class 8-3. The use of Kahoot in this study went through pre-test and post-test stages. The results of student assessment in the pretest or before the application of learning media reached an average of 74.85 with a poor category, and the results of student assessment in the posttest or after the application of Kahoot learning media reached an average of 83.00 with a good category. Therefore, there is a difference between the pretest and posttest results. The Shared Sample Test results show that the significant value (sig2-tailed) of 0.006 is below 0.05, which indicates that the t-table is the t-statistic. Therefore, H0 is rejected and Ha is accepted, which indicates that students of class VIII-3 of SMP IT Daarul Istiqlal Marindal I experienced a much greater increase in vocabulary after using Kahoot learning media.